Addictive organization - Schaef, Anne Wilson (Harper San FranciscoUS, 1990)
Defines terms including addiction, substance addiction, addictive process and, addictive system. Describes characteristics of the addictive system including: confusion, dishonesty, perfectionism and, self-centeredness. Discusses four major forms of addiction in organizations, and discusses the role of the consultant in the recovery process of an addictive organization. Identifies characteristics of a recovering organization including: self-responsibility; multivaried - multidirectional communication; mission supported by structure; and, commitment to a process model of change.